Mechanical responses of triply periodic minimal surface gyroid lattice structures fabricated by binder jetting additive manufacturing - Yingmi Xie; Yiwei Mao; Yuhua Heng; Jianquan Tao; Lin Xiang; Xiuyuan Qin; Qingsong Wei (Journal of Materials Research and Technology)
Lattice structures with triply periodic minimal surface (TPMS) are promising in many applications, such as bone implantation and aerospace field. The binder jetting (BJ) additive manufacturing technique offers advantages such as low cost and high rate, with the potential to enabling the widespread application of these structures in these fields. In this study, sheet-based uniform gyroid lattice structures (U-GLS) and graded gyroid lattice structures (G-GLS) with different relative densities were fabricated by the BJ for the first time, achieving good precision. The compressive property and the deformation behaviors of the GLS fabricated by BJ were investigated. Additionally, finite element (FE) strategy was developed for modeling the deformation mechanism of the GLS fabricated by BJ. The results showed that during the compression deformation process, the U-GLS exhibited fracture in the direction of the 45° angle along the lattice stress surface, and the G-GLS exhibited layer-by-layer fracture from the low-relative-density lattice layer to the high-relative-density lattice layer. The U-GLS fabricated by BJ exhibited higher yield strength, excellent plastic deformation ability, and good energy absorption capacity, while the G-GLS demonstrated stable strength and energy absorption efficiency. The FE method can describe and predict the mechanical properties and deformation behaviors of the GLS with Ti6Al4V alloy as the base material.